PROBLEMS OF EDUCATIONAL POLICY IN BUKHARA IN THE LATE XIX-EARLY XX CENTURY AND THEIR SOLUTIONS - Sobirov Ulug‘bek G‘ofurovich (International Journal of Innovations in Engineering Research and Technology, 2022)
This article highlights the main changes in the public education system of the Bukhara People's Republic after its formation, the education policy, the Department of Public Education established in the republic, the creation of schools, training courses, higher educational institutions, funds allocated for education, textbooks and the like.